Efficacy and safety of renal denervation in elderly patients with resistant hypertension. Issue 2 (August 2015) - Ziegler, Ann‐Kathrin; Bertog, Stefan; Kaltenbach, Benjamin; Id, Dani; Franke, Jennifer; Hofmann, Ilona; Vaskelyte, Laura; Sievert, Horst
<x xml:space="preserve">Abstract</x> Background: Catheter‐based renal sympathetic denervation (RD) causes significant blood pressure (BP) reductions in patients with resistant hypertension (rHTN). However, hypertensive elderly patients reportedly have a lower sympathetic tone than younger patients and a BP lowering effect of RD in this population has not yet been demonstrated. The purpose of this study was to assess the efficacy and safety of RD in elderly patients. Methods: We reviewed all consecutive patients aged ≥ 75 years (mean: 78 years) with rHTN treated with RD. Twenty‐four patients were included in this prospective study. Office and ambulatory BPs were assessed at baseline and 6‐months follow‐up. Primary endpoint was the change in office systolic BP at 6 months. Results: Baseline mean office BP was 173/86 ± 21/13 mm Hg. Baseline 24‐hr mean ambulatory BP, available in 22 patients, was 158/80 ± 20/13 mm Hg. Baseline creatinine was 1.0 ± 0.18 mg/dl and mean number of antihypertensive agents at baseline 4.3 ± 1.4. No device‐ or procedure‐related adverse events occurred. At 6‐months follow‐up, the mean office BP decreased by 19/11 ± 29/16 mm Hg (P < 0.01 compared to baseline). Mean systolic 24 hr ambulatory BP, available in 17 patients, decreased by 9/5 ± 13/13 mm Hg. Antihypertensive medications could be reduced in nine patients. Furthermore, renal function was not impaired. Conclusion: According to our findings, a similar magnitude of BP reduction as reported in previous trials can be expected in elderly patients. Elderly patients with rHTN should not be excluded from renal denervation. © 2015 Wiley Periodicals, Inc.